Digital Transformation Based on Technological Innovations (Texas Journal of Engineering and Technology, 2022)
The application of technological digital platform in the creation of design development, the most important factors of an innovative economy, is considered. It is shown that the digital platform is the basis for designing the main links of the technological chain. The concept of the ecosystem and the object of the innovation structure is given